الحاجات الإرشادية لطلبة مدارس الموهوبين بولاية الخرطوم Students’ Counseling Needs at Gifted Schools in Khartoum State - Al-Hidabi, Dawood Abdulmalek Yahya; Abdullwalli, Eshrak (University of Science and Technology, Yaman, 2019)
The study aimed at investigating the students’ counselling needs at gifted schools in Khartoum. The sample of the study consisted of 172 out of 258 students. 86 were male students and 86 were female students from three education districts namely Khartoum, Umdarman and Bahri. A questionnaire of 72 items was developed, standardized and distributed. Then, data was collected and analysed using SPSS package. The results showed that the counselling needs for the gifted sample vary. Health Counselling needs were high and the family counselling needs were second in ranking whereas the results of the rest dimensions namely school, social and professional counselling needs were low. The study concluded with a set of recommendations particularly in the area of health counselling needs as well as strengthening the cooperation between schools’ counsellors and parents.